FILSAFAT WUJUDIYAH (Perspektif Mu’tazilah, Filsuf Islam dan Alquran) - Adenan Adenan (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2019)
Al-Wujud's philosophy "exists," is the most abstract concept. Therefore, there are two opinions in response to this. One way is to assume that "there" cannot be defined or captured by the mind, but can only be directly captured by intellectual intuition. This may be acceptable to the minds of most people, but is "There" God too? Of course, there are people who argue that "There" is something absolute that is not the same as "There" is something relative. However, this is not the case with Mulla Sadra (philosopher of Isfhan) who argues that "Ada" is single and all for all objects, both concrete and abstract. Nevertheless "There" is God is "There" is pure, while "There" is the other mixed with essence. Because God is pure "There", saying "God does not exist" is an impossibility. If God does not exist, it means that "There" is not there. Isn't that an impossibility? Therefore, God is absolutely necessary (Wajib al-Wujud). Because "There is no" is a contradiction, the opposite statement is true.